An atypical pulmonary presentation of Sjögren's Syndrome - Juan M Garcia Puebla; Arnaldo Nieves Ortiz; Kyomara Hernández Moya; Kimberly C Padilla Rodríguez; Ileana Rivera Burgos; María C Betancourt Quiles; Ricardo Fernández González (Open Journal of Orthopedics and Rheumatology - Peertechz Publications, 2020)
Sjögren's syndrome is an autoimmune disease characterized by exocrine glands lymphocytic infiltration. However, some manifestations can happen outside the secretory glands affecting multiple organs. We report a 63-year-old man without previous history of any rheumatologic disease and negative arthralgias, mucosal or ocular dryness, in which findings of chest CT scan were consistent with interstitial lung disease prompting further diagnostic workup. Given the serological results, Sjögren's syndrome was highly suspicious in our diagnosis for which a lip biopsy was performed revealing the etiology of our patient's interstitial lung changes. To our knowledge, respiratory symptoms are rarely the initial presentation of this disease, heightening a more thorough workup for a patient with interstitial lung disease with an unclear clinical association requiring a biopsy.